Bone-implant contact around crestal and subcrestal dental implants submitted to immediate and conventional loading - Pontes, Ana Emília Farias; Ribeiro, Fernando Salimon; Iezzi, Giovanna; Pires, Juliana Rico; Zuza, Elizangela Partata; Piattelli, Adriano; Marcantonio Júnior, Elcio [UNESP] (Hindawi, 2014)
The present study aims to evaluate the influence of apicocoronal position and immediate and conventional loading in the percentage of bone-implant contact (BIC). Thus, 36 implants were inserted in the edentulous mandible from six dogs. Three implants were installed in each hemimandible, in different positions in relation to the ridge: Bone Level (at crestal bone level), Minus 1 (one millimeter apical to crestal bone), and Minus 2 (two millimeters apical to crestal bone). In addition, each hemimandible was submitted to a loading protocol: immediate (prosthesis installed 24 hours after implantation) or conventional (prosthesis installed 120 days after implantation). Ninety days after, animals were killed, and implant and adjacent tissues were prepared for histometric analysis. BIC values from immediate loaded implants were 58.7%, 57.7%, and 51.1%, respectively, while conventional loaded implants were 61.8%, 53.8%, and 68.4%. Differences statistically significant were not observed among groups (𝑃 = 0.10, ANOVA test). These findings suggest that different apicocoronal positioning and loading protocols evaluated did not interfere in the percentage of boneimplant contact, suggesting that these procedures did not jeopardize osseointegration.